Sclerotinia Diseases of Crop Plants: Biology, Ecology and Disease Management - Saharan, G. S.; Mehta, Naresh (Springer Netherlands : Imprint: Springer, 2008)
Sclerotinia is one of the most devastating and cosmopolitan soil borne plant pathogen that infects more than 500 species of plants worldwide including field crops, fruit crops, ornamentals, trees, shrubs and numerous weeds. Annual yield losses due to Sclerotinia diseases exceed over millions of dollars each year world over. Extensive crop damage, lack of high levels of host resistance and the general difficulty of managing diseases caused by Sclerotinia have been the impetus for sustainable research on this pathogen. The present book on Sclerotinia deals with the aspects on taxonomy, nomenclature, geographical distribution, economic importance, host range, the diseases caused, symptomatology, disease assessment, reproduction, ultra-structures, pathogenic variability, perpetuation, infection and pathogenesis, biochemical, molecular and physiological aspects of host pathogen interaction, seed infection, disease cycle, epidemiology and forecasting, host resistance and disease management strategies. In addition, laboratory and field techniques developed so far for Sclerotinia have been included. Some newly emerging areas of Sclerotinia research include its application as myco-herbicide, phytoalexin elicitors, hypovirulence, volatile compound imitator, sporigermin production from sclerotia, resistance to fungicides and health hazard's due to Sclerotinia diseases have been discussed. The subject matter is vividly illustrated with photographs (macroscopic, microscopic, electron micrographs, scanning electron micrographs), drawings, figures, histograms, graphs, tables and flow charts of techniques which make it more interesting, stimulating, effective and easy to understand by the readers. This is the first ever comprehensive compilation on different aspects of Sclerotinia and will be immense value for researchers, teachers and students.